Dynamic effective stress analysis of a site with liquefiable interlayer: considering vertical and horizontal ground motion - Peng, Xiao-Bo; Gao, Yuan; Xue, Ying-Ying; Tao, Xiao-San; Xu, Ling-Yu (Frontiers in Earth Science, 2024)
This study uses a fully coupled dynamic effective stress analysis method to evaluate the seismic response of a site containing silty sand which is a liquefiable interlayer. A generalized plasticity model is employed to describe the liquefaction behavior of silty sand under seismic action, and a nonlinear constitutive model is used to account for the nonlinear and hysteretic characteristics of non-liquefiable soils. The parameters of constitutive model were calibrated from the shear wave velocity and results of resonant column tests on different soils in a borehole. The results indicated that (1) A new spike with a period of approximately 1 s was observed at the top of the liquefiable interlayer compared to that at the bottom of the interlayer, reflecting a common seismic response characteristic induced by the rise in the excess pore water pressure (EPWP); (2) The low-frequency input motion caused higher EPWP within the liquefiable interlayer and more ground settlement at the consolidation stage; (3) The increase in either peak horizontal acceleration or peak vertical acceleration of input motions resulted in higher increase in the EPWP and ground surface settlement. Moreover, the vertical seismic component in near-field earthquakes has much more significant effect on the ground settlement in liquefiable sites than that in far-field earthquakes.